Auditory verbal hallucinations and continuum models of psychosis: A systematic review of the healthy voice-hearer literature. (February 2017) - Baumeister, David; Sedgwick, Ottilie; Howes, Oliver; Peters, Emmanuelle
Abstract: Recent decades have seen a surge of research interest in the phenomenon of healthy individuals who experience auditory verbal hallucinations, yet do not exhibit distress or need for care. The aims of the present systematic review are to provide a comprehensive overview of this research and examine how healthy voice-hearers may best be conceptualised in relation to the diagnostic versus 'quasi-' and 'fully-dimensional' continuum models of psychosis. A systematic literature search was conducted, resulting in a total of 398 article titles and abstracts that were scrutinised for appropriateness to the present objective. Seventy articles were identified for full-text analysis, of which 36 met criteria for inclusion. Subjective perceptual experience of voices, such as loudness or location (i.e., inside/outside head), is similar in clinical and non-clinical groups, although clinical voice-hearers have more frequent voices, more negative voice content, and an older age of onset. Groups differ significantly in beliefs about voices, control over voices, voice-related distress, and affective difficulties. Cognitive biases, reduced global functioning, and psychiatric symptoms such as delusions, appear more prevalent in healthy voice-hearers than in healthy controls, yet less than in clinical samples. Transition to mental health difficulties is increased in HVHs, yet only occurs in a minority and is predicted by previous mood problems and voice distress. Whilst healthy voice-hearers show similar brain activity during hallucinatory experiences to clinical voice-hearers, other neuroimaging measures, such as mismatch negativity, have been inconclusive. Risk factors such as familial and childhood trauma appear similar between clinical and non-clinical voice-hearers. Overall the results of the present systematic review support a continuum view rather than a diagnostic model, but cannot distinguish between 'quasi' and 'fully' dimensional models. Healthy voice-hearers may be a key resource in informing transdiagnostic approaches to research of auditory hallucinations. Highlights: Subjective perceptual experiences of voices appear similar in clinical and non-clinical groups. Healthy voice-hearers hear voices less frequently, with less negative content, more perceived control and from an earlier age. Healthy and clinical voice-hearers differ in beliefs about voices, voice-related distress, and affective difficulties. Healthy voice-hearers show more cognitive biases, psychiatric symptoms and functional impairments than healthy controls. Risk factors such as familial and childhood trauma appear similar between clinical and non-clinical voice-hearers.